Augmented Reality in Child Education: A Bibliometric and Trend Analysis of Global Research (2015–2025) - Yelva Nofriyanti; Andika Bayu Putra; Desmawati Roza; Evi Desmariani; Meria Ultra Gusteti (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to bibliometrically analyze publication trends, collaboration patterns, and research development directions regarding Augmented Reality (AR) in children's education. Data was obtained from the Scopus database on July 16, 2025 with the keywords "augmented reality, education, learning, teaching", which resulted in 178 initial documents and, after going through the exclusion inclusion screening process, were selected into 71 articles. All data were verified and analyzed using VOSviewer through citation map construction, keyword visualization, author collaboration, and publication distribution by journal, institution, and country. The results show that publications on AR in children's education increased significantly in the period 2015–2025, with a peak in 2024, as well as emerging research hotspots in interactive learning activities, language learning, early childhood education, and support for children with special needs such as Autism Spectrum Disorder (ASD). The collaborative analysis confirms the major contributions of Asian countries, particularly Indonesia, Turkey, Malaysia, and Taiwan, in the development of this literature. Overall, the findings confirm that AR plays an important role in increasing children's motivation, engagement, concept understanding, and social-emotional interaction, although they still face obstacles in the form of limited infrastructure, digital literacy of educators, and lack of longitudinal research. Therefore, further research with a more rigorous design, more diverse participants, and a focus on sustainability and curriculum integration is needed to optimize the implementation of AR as a pedagogical innovation in children's education.